Polymorphous granular cells in the lung of the primitive fish, the bichir Polypterus senegalus. (13th December 2015) - Zaccone, Daniele; Icardo, Jose Manuel; Kuciel, Michał; Alesci, Alessio; Pergolizzi, Simona; Satora, Leszek; Lauriano, Eugenia Rita; Zaccone, Giacomo
Abstract: This study describes the distribution and the coexpression of specific neurochemical markers in both neuroendocrine‐like cells (NEC‐like) and polymorphous granular cells (PGCs) that populate the mucociliated epithelium of the lung in the air‐breathing fish Polypterus senegalus, using confocal immunohistochemistry. Using confocal immunohistochemistry, we determined the coexpression of specific neurochemical markers. Colocalization studies showed that 5HT is coexpressed with calbindin and nNOS and choline acetyltransferase (ChAT) is coexpressed with nNOS in the PGCs. This study also shows for the first time the simultaneous occurrence of piscidin 1 and 5HT in the PGCs. The function of these cells being equivalent to ones found in fish gill subepithelial parenchyma is still not known. Due to the importance of piscidin 1 in local immune defence, more research is to be useful to understand a possible interaction of PGCs with immune response in the bichir lung. In fact, the capacity of PGCs to produce NO and other neuroactive substances found in immune cells of fish may represent a primitive form of immunoregulation of innate immunity and specifically antimicrobial function as NO induction and respiratory burst activity are correlated with immune response.